Abordagem das capacitações : uma defesa da inclusão do transtorno de depressão na dimensão saúde - Vieweger, Pedro (2020)
According to the World Health Organization (WHO), silent diseases, caused by compromised mental health, impacts on personal life and on society as well as diseases caused by poor physical health. One of these mental health conditions it’s the depression that today is considered the medical condition most spread worldwide and a serious health problem. According to WHO data, more than 300 million peoples worldwide are suffering with depression and, up until 2030, depression will be the most cause of global diseases. Considering the emergence of this theme, this dissertation investigated how depression is related to development economics, more specifically with the Capability Approach, that is an approach that considers important individual aspects and individual concerns. In the bibliographic survey between mental health issues and the Capability Approach, it was possible to identify that there are few academic papers, only 8 between the years 2009 and 2018. Considering that this is a recent topic and that have publications lacks, in this dissertation is performed one defense to include depression on health dimension in the Capability Approach. To realize this, after making a review of theoretical fundamentals about depression disorder, it was listed situations when depression can be a wall to elementary and non-elementary functionings in Amartya Sen. Plus, looking to women's privations in Martha Nussbaum, were exemplified the circumstances of deprivation and violence that can cause depression in women's. In conclusion, it is proposed here that depression can be an important wall for peoples to achieve their functionings and to live a life that they want, as well as privations, inequality and violence can cause depression. For these reasons, it is argued here that depression disorder needs to be considered as a relevant aspect in the health dimension, mainly in the Capability Approach application.